2005
DOI: 10.1111/j.1528-1167.2005.00289.x
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenesis and Reduced Inward Rectifier Potassium Current in Tuberous Sclerosis Complex‐1–Deficient Astrocytes

Abstract: Summary:Purpose: Individuals with tuberous sclerosis complex (TSC) frequently have intractable epilepsy. To gain insights into mechanisms of epileptogenesis in TSC, we previously developed a mouse model of TSC with conditional inactivation of the Tsc1 gene in glia (Tsc1 GFAP CKO mice). These mice develop progressive seizures, suggesting that glial dysfunction may be involved in epileptogenesis in TSC. Here, we investigated the hypothesis that impairment of potassium uptake through astrocyte inward rectifier po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 58 publications
(94 reference statements)
2
81
0
Order By: Relevance
“…An increase in cortical neurons excitability has been described in mice with reduced Kir currents and lower expression of Kir2.1 and Kir6.1 channel subunits (Jansen et al, 2005). It has also been shown that extracellular K ϩ increases in Kir4.1 Ϫ/Ϫ mice (Neusch et al, 2006;Djukic et al, 2007), and, although an increase in neuronal excitability was not reported, in one case there was an enhancement of synaptic potentiation.…”
Section: Discussionmentioning
confidence: 91%
“…An increase in cortical neurons excitability has been described in mice with reduced Kir currents and lower expression of Kir2.1 and Kir6.1 channel subunits (Jansen et al, 2005). It has also been shown that extracellular K ϩ increases in Kir4.1 Ϫ/Ϫ mice (Neusch et al, 2006;Djukic et al, 2007), and, although an increase in neuronal excitability was not reported, in one case there was an enhancement of synaptic potentiation.…”
Section: Discussionmentioning
confidence: 91%
“…This was unexpected, considering that astrocytes in human tubers show increased GFAP immunoreactivity and cell size and loss of GS (28,34). We did not explore other features such as K + channel and glutamate transporter expression that are altered in epileptic astrocytes or Tsc1 null astrocytes (36,(50)(51)(52). However, human tubers, which have variable degrees of gliosis, are removed from patients who undergo surgical treatment for focal epilepsy mapped to the resected tubers (53).…”
Section: Discussionmentioning
confidence: 99%
“…The K 1 siphoning process in the cortex may involve different mediators than in the retina where it has been suggested that Kir2.1 channels, in retinal M€ uller (glial) cells, may be responsible for K 1 influx within the synaptic layers, whereas Kir4.1 channels may be mainly responsible for K 1 release into the vitreous and the blood vessels (Kofuji and Newman, 2004;Kofuji et al, 2002). Expression of functional Kir2-type channel subunits in astrocytes remains controversial (Jansen et al, 2005;Pruss et al, 2005;Schr€ oder et al, 2002;Stonehouse et al, 1999). However, in the present study, we demonstrate an almost Fig.…”
Section: Maintenance Of a Hyperpolarized Membrane Potentialmentioning
confidence: 98%
“…The most obvious is that elevations in potassium due to decreased potassium buffering will lead to hyperexcitability of neurons and, ultimately, to seizures. Indeed, Jansen et al (2005) have recently demonstrated alterations of Kir channels in astrocytes associated with epileptogenesis in a mouse model of the tuberous sclerosis complex. Furthermore, mislocalization of aquaporin-4 which is normally colocalized with Kir4.1 protein (Nagelhus et al, 1999(Nagelhus et al, , 2004 results in delayed K 1 clearance and increased seizure activity in mice (Amiry-Moghaddam et al, 2003).…”
Section: Potential In Vivo Consequences Of Reducedmentioning
confidence: 99%